Lifetime calculation of adhesively bonded joints under proportional and non-proportional multiaxial fatigue loading: a combined critical plane and critical distance approach. Issue 6 (26th April 2022) - Fernandes, P.H.E.; Poggenburg-Harrach, L.; Nagel, C.; Beber, V.C.
ABSTRACT: This work presents an approach for lifetime calculation of adhesively bonded joints under proportional and non-proportional multiaxial fatigue loads. In-phase and out-of-phase fatigue data with varying stress ratio ( R = 0.1 and −1.0) from several joint geometries (butt, scarf, thick adherend shear test and butt-bonded double pipe joints) was employed. The approach is based on the stress-life concept and the Theory of Critical Distances (TCD) considering point and line methods. Stresses were calculated using 2D-FEA with linear-elastic and elastoplastic adhesive behaviours. Non-proportional stresses were addressed by the Maximum Rectangular Hull method. Three failure criteria were investigated: Drucker-Prager (DPC): an invariant-based equivalent stress criterion; Findley (FC): a critical plane stress-based criterion; (c) Fatemi-Socie (FSC): a critical plane stress-strain-based criterion. The material parameter of each failure criterion was iteratively calibrated using fatigue data. The FSC had the worst prediction performance. The DPC presented good agreement with in-phase data, but less robust as the variation of its material parameter changed considerably the prediction accuracy. For both DPC and FC, the line method and linear-elastic models were capable of providing good predictions. The FC yielded the best predictions considering a normal sensitivity bF > 1.0 for different stress ratios, in-phase and out-of-phase loads.